Improved Outcome of Severe Acute Pancreatitis in the Intensive Care Unit. (21st February 2013) - Pavlidis, Polychronis; Crichton, Siobhan; Lemmich Smith, Joanna; Morrison, David; Atkinson, Simon; Wyncoll, Duncan; Ostermann, Marlies
Abstract : Background . Severe acute pancreatitis (SAP) is associated with serious morbidity and mortality. Our objective was to describe the case mix, management, and outcome of patients with SAP receiving modern critical care in the Intensive Care Unit (ICU). Methods . Retrospective analysis of patients with SAP admitted to the ICU in a single tertiary care centre in the UK between January 2005 and December 2010. Results . Fifty SAP patients were admitted to ICU (62% male, mean age 51.7 (SD 14.8)). The most common aetiologies were alcohol (40%) and gallstones (30%). On admission to ICU, the median Acute Physiology and Chronic Health Evaluation (APACHE) II score was 17, the pancreatitis outcome prediction score was 8, and the median Computed Tomography Severity Index (CTSI) was 4. Forty patients (80%) tolerated enteral nutrition, and 46% received antibiotics for non-SAP reasons. Acute kidney injury was significantly more common among hospital nonsurvivors compared to survivors (100% versus 42%, P = 0.0001 ). ICU mortality and hospital mortality were 16% and 20%, respectively, and median lengths of stay in ICU and hospital were 13.5 and 30 days, respectively. Among hospital survivors, 27.5% developed diabetes mellitus and 5% needed long-term renal replacement therapy. Conclusions . The outcome of patients with SAP in ICU was better than previously reported but associated with a resource demanding hospital stay and long-term morbidity.